Fifteen-Year Prospective Analysis of Television Viewing and Adiposity in African American and Caucasian Men and Women: The CARDIA Study. (11th August 2015) - Chen, Chung-Yu; Pereira, Mark A.; Kim, Kevin H.; Erickson, Darin; Jacobs, David R.; Zgibor, Janice C.; Chung, Tammy; Sidney, Stephen; Iribarren, Carlos; Fabio, Anthony
There are limited data from long-term prospective studies on the association between television (TV) viewing and obesity. We investigated this association between TV viewing and body mass index (BMI) and waist circumference (WST) over 15 years on 3, 269 participants from the Coronary Artery Risk Development in Young Adults (CARDIA) study. We used cross-lagged panel models at exam Years 5, 10, 15, and 20 over 15 years to assess the association between TV viewing and obesity. The cross-lagged effects of TV viewing on anthropometry were significant from exam Year 5 to Year 10 ( B = 0.034 for BMI and 0.036 for WST). However, the cross-lagged effects of TV viewing at Years 10 and 15 on obesity at Years 15 and 20, respectively, were nonsignificant. The findings indicate that higher levels of TV viewing predicted higher BMI and WC in young adulthood, but this association was not observed as individuals aged over the following decade.